2017
DOI: 10.1016/j.bandl.2015.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Sleep-based memory processing facilitates grammatical generalization: Evidence from targeted memory reactivation

Abstract: Generalization — the ability to abstract regularities from specific examples and apply them to novel instances — is an essential component of language acquisition. Generalization not only depends on exposure to input during wake, but may also improve offline during sleep. Here we examined whether targeted memory reactivation during sleep can influence grammatical generalization. Participants gradually acquired the grammatical rules of an artificial language through an interactive learning procedure. Then, phra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
37
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(46 citation statements)
references
References 56 publications
9
37
0
Order By: Relevance
“…In humans, behavioral work has shown that rule acquisition and use is more evident with a temporal delay (Sweegers and Talamini, 2014). Similarly, other work suggests that sleep enhances transitive inference behavior (Ellenbogen et al, 2007; Lau et al, 2010) and benefits the extraction and generalization of statistical regularities across motor and acoustic patterns (Wagner et al, 2004; Durrant et al, 2011, 2013; Batterink and Paller, 2017). However, few studies to date have shed light on how the underlying neural representations of memories with shared features are transformed over time.…”
Section: Introductionmentioning
confidence: 88%
“…In humans, behavioral work has shown that rule acquisition and use is more evident with a temporal delay (Sweegers and Talamini, 2014). Similarly, other work suggests that sleep enhances transitive inference behavior (Ellenbogen et al, 2007; Lau et al, 2010) and benefits the extraction and generalization of statistical regularities across motor and acoustic patterns (Wagner et al, 2004; Durrant et al, 2011, 2013; Batterink and Paller, 2017). However, few studies to date have shed light on how the underlying neural representations of memories with shared features are transformed over time.…”
Section: Introductionmentioning
confidence: 88%
“…Whether TMR can be used in a similar way to promote memory reorganisation and processes of abstraction and generalisation is largely unknown. The first evidence in support of this hypothesis was provided in a recent study by Batterink and colleagues 37 who…”
Section: Introductionmentioning
confidence: 48%
“…A recent study by Batterink and colleagues 37 , which provided the first evidence that TMR can manipulate grammatical generalisation during sleep, also used memory cues that did not vary probabilistically. Based on these results the question arises whether partially overlapping memory cues might have the potential to disrupt the beneficial effect of sleep on memory reorganisation.…”
Section: Discussionmentioning
confidence: 99%
“…When they woke, they knew the meanings of the words presented while they were asleep better than for those not presented while they were asleep. In a similar study, we improved the learning of rules of grammar important for learning a new language [4]. We also strengthened musical skills during sleep [5].…”
Section: Memory Hackingmentioning
confidence: 85%